Morfología lingual del murciélago piscívoro Noctilio leporinus (Chiroctera: Noctilionidae) - Elizalde-Arellano, Cynthia; Uria-Galicia, Esther; López-Vidal, Juan Carlos (Instituto de Ecología, A.C., 2020)
The anatomy and histology of the tongue of Noctilio leporinus, a mainly piscivorous bat, were studied to search for any special character which could be associated to this feeding type. The surface of the tongue has three kinds of papillae: filiform, fungiform and circumvallate. At the histological level, only the two last ones have taste buds. The circumvallate are connected to the Von Ebner serous glands. There is a medial vertical septum at the center of the tongue. At both sides of it there are pairs of veins, arteries, and nervous fibers. Among muscular fibers there are mucous glands in the ventral side. At the distal portion of the tongue, there is a pair of tonsils with inmunological function, each one surrounded by a large mucous gland which can be seen at naked eye. The tonsils and the large mucous glands are the only specialized structures founded in the tongue of N. leporinus, which could be associated to the piscivorous feeding type. This is the first record of these structures in Chiroptera.